Carbon Footprint Impact, of Monoclonal Antibodies for Severe Asthma, Administered in Italy - Diego Bagnasco; Laura Pini; Benedetta Bondi; Carola Montagnino; Elisa Testino; Veronica Capuano; Celeste Pugliaro; Luisa Brussino; Stefania Nicola; Marco Caminati; Ilaria Baiardini; Fulvio Braido (Biomedicines)
Background: Severe asthma is a respiratory condition, involving treatments (i.e., inhaled steroids, systemic steroids, hospitalization) capable of increasing significant carbon footprint, raising concerns about environmental sustainability in healthcare. Sustainable healthcare policies and use of environmentally friendly treatment options are crucial in balancing effective asthma management with climate responsibility. Objectives: With this manuscript, we want to assess the impact, in terms of CO2 production, of patients suffering from severe asthma and treated with biological drugs, to show the reduction in carbon footprint after the use of these drugs compared to the time when they were not prescribed. We analyzed data from three studies, all conducted in real life in Italy, of patients treated with mepolizumab, benralizumab and dupilumab, for the control of severe asthma. Methods: Data on number of exacerbations and hospitalizations, systemic corticosteroids (CS) cycles and their dose, were collected by three already published real-life trials, on the above-mentioned biologics, and used to calculate carbon footprint impact before and after biological therapy. For the mepolizumab study, the data collected referred to patients who started the drug between June 2017 and January 2019; for dupilumab, there were no age limits with patients enrolled between December 2019 and July 2020, whereas in the benralizumab study, all patients had to be over 18 years old. The statistical analysis was performed with Shapiro–Wilk test, t test and Cohen’s test. Results: The use of biologic drugs showed a significant reduction in CO2 production after the introduction of these therapies, mainly secondary to a reduction in exacerbations, hospitalizations and CS use. In numerical terms, an average reduction of 75% in CO2 production, per patient, is shown. Conclusions: Disease control, clinical remission of disease, in patients with severe asthma is certainly a determining factor in assessing the effectiveness of a treatment. Provided these goals are achieved, biological drug therapy has also proved to be particularly virtuous from the fundamental environmental point of view, allowing a significant reduction in CO2 production for the management of these patients.